O crescimento e a expansão urbana e industrial no município de Extrema, Minas Gerais, a partir da duplicação da Rodovia Fernão Dias, BR 381 - Fonseca, Carlos Eduardo (2009)
This thesis approaches the urban and industrial growth and development of city of Extrema, located in the southern state of Minas Gerais, from the duplication of Rodovia Fernão Dias, BR 381, which links the capital of São Paulo to Belo Horizonte. In the analysis of the city the matters referred to the environment are considered, in order to understand how the urban sprawl and the respect for nature are reconciled. In addition to stand out in the south of Minas Gerais due to the attraction of industrial companies, Extrema shows promising prospects for the development of the local tourism, because of its waterfalls and mainly, the Serra do Lopo. The city located in a strong and strategic position, near the capital of São Paulo in the area of influence of the Highway, in recent years has shown strong growth and economic development because of the attraction of new industries and job creation. In this study, it is intended to understand Extrema in the context of the devolution process occurred mainly due to industrial overflow of the metropolitan region of Sao Paulo and the "war tax" between states and municipalities. It examined how the city reconciles economic development and sustainability, also taking advantage of the potential for tourism because of the beautiful scenery that the region offers, and preventing that the growth of the industries and tourism can cause environmental impacts